Students Motivation Levels and Barriers to Learning Physical Education: Senior High School Perspective - Sirojul Muhyi, Dinta Dwi; Kurniawan, Rama; Saputra, Surya Adi (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This study investigated high school students motivation and barriers to implementing Physical Education (PE). This study used a descriptive quantitative research survey method involving 300 samples. The instrument utilizes an online motivation questionnaire for data collection. The data is analyzed using percentage analyses. The results of data analysis with indicators of student motivation reveal that the Intrinsic motivation and Identified regulation categories have higher results and identical values, with a value of 23%, and the Amotivation category, with a value of 15%, has lower results among other motivation indicators including intrinsic motivation, identified regulation, introjected regulation, external regulation. The indicator of student barriers shows that the external category has higher results with a value of 54%, and the internal category has lower results with a value of 46%. This research indicates that intrinsic motivation and identified regulation have identical values and are higher than the other motivation categories. It concludes that many students still have the motivation that grows from themselves and pressure from outside to participate in physical education learning. Barriers can also be concluded by examining higher external than internal indicators. This study shows that students have barriers that prevent them from growing outside to participate in educational learning activities.